Social inequality and perceptions of quality in Argentina's urban educational offer - Ianina Tuñón; Verónica Halperin (Universidad Autónoma de Baja California, 2010)
This paper is an attempt to offer a diagnosis of the magnitude and characteristics of educational segmentation, through social inequality in access to educational resources in both public and private education. It shows how children and adolescents in the same educational level have unequal access to resources (rights) according to their socioeconomic status. Taken as an indicator of learning segmentation is the educational offer to which children and adolescents have access in primary and secondary school, aspects promoted in the National Education Law (Law No. 26,206). As well, we will explore social representations concerning the quality of education in public and private schools based on the evaluation made by parents and/or guardians.